The establishment, status and activities of the first Association of officials of the Islamic community in socialist Bosnia and Herzegovina - Bećirović, Denis (Historical Thought, 2025)
The author, using published and unpublished sources, analyzes the formation and activities of the Association of officials of the Islamic Community in Bosnia and Herzegovina in the first post-war decade. Also the structure and organization of the Association was presented, including material provision of the Association members, assisting members in the performance of their religious duties and the influence of the Association on the promotion of religious and moral life. The text, based on reliable sources, indicates that the management of the Association of Ilmija in this period only formally expressed the interests and opinions of their membership. In reality, however, the Association was just a cover under which the communist government realized its goals.